Analisis Kemampuan Komunikasi Matematis Mahasiswa pada Materi Geometri - Turmuzi, Muhammad; Wahidaturrahmi, Wahidaturrahmi; Kurniawan, Eka (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
The purpose of this study was to determine the mathematical communication skills of prospective elementary school teacher students on Geometry material. This research method is descriptive qualitative analyzed from the given instrument. The instrument in this study was in the form of 4 written test questions. The subjects of this study were 34 students in the Primary School Teacher Education Study Program, FKIP, Mataram University. The indicators used in this study are 4 indicators of mathematical communication skills, namely explaining mathematical ideas in the form of images, explaining ideas, situations in written form, connecting images to mathematical ideas and reading with the understanding of a written mathematical representation. From the results of data analysis, it was found that the students' mathematical communication skills in the Geometry material were in the very low category. This can be seen from the results of the recapitulation of student answers and the results of the conversion of student scores with the successive percentages of 45.58% and 50%, especially in questions with reading indicators with an understanding of a mathematical representation.